A model of motivational and technological factors influencing massive open online courses’ continuous intention to use - Al-Shami, Samer Ali Hussein; Aldahmani, Salem Abdulla Saif Shabib; Kamalrudin, Massila; Al-Kumaim, Nabil Hasan Saleh; Al Mamun, Abdullah; Al-shami, Mohammed; Jaber, Mustafa Musa (MDPI, 2022)
Massive open online courses have been regarded as effective technological innovations that improve educational systems in the era of digitalisation. However, only 10% of the registered students complete their courses. This study aims to examine the motivational and technological factors and contextual features on students’ continuous intention to use. A questionnaire was gathered from 315 of students in the UAE and revealed that social motivational and technological factors driven by the technology acceptance model and technology task fit theory significantly influenced the students’ continuance intention to use. This study also revealed that contextual features including language use and course accreditation are important indicators determining students’ behaviours toward the use. Hence, this study proposed an integrative model to explain ways to improve continuance intention to use. This study contributes to the sustainable use of massive open online courses in developing countries through an integrative model.